From shares to machines: How common ownership drives automation - Joseph Emmens; Dennis Hutschenreiter; Stefano Manfredonia; Felix Noth; Tommaso Santini (Halle Institute for Economic Research (IWH), 2024)
Does increasing common ownership influence firms' automation strategies? We develop and empirically test a theory indicating that institutional investors' common ownership drives firms that employ workers in the same local labor markets to boost automation-related innovation. First, we present a model integrating task-based production and common ownership, demonstrating that greater ownership overlap drives firms to internalize the impact of their automation decisions on the wage bills of local labor market competitors, leading to more automation and reduced employment. Second, we empirically validate the model's predictions. Based on patent texts, the geographic distribution of firms' labor forces at the establishment level, and exogenous increases in common ownership due to institutional investor mergers, we analyze the effects of rising common ownership on automation innovation within and across labor markets. Our findings reveal that firms experiencing a positive shock to common ownership with labor market rivals exhibit increased automation and decreased employment growth. Conversely, similar ownership shocks do not affect automation innovation if firms do not share local labor markets.
Keywords: G23; J23; L22; O32; O33; 330; automation; common ownership; local labor markets; market power